(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
Two samples of seed materials of the under utilized tribal pulse, D. lablab var. vulgaris (dark brown and pale brown coloured seed coat) were collected from Anakodi, Krishnagiri district, Eastern Ghats, Tamil Nadu. The mature seed samples were analysed for proximate composition, mineral profiles, vitamins, seed protein fractions, fatty acid profiles, amino acid profiles and antinutritional factors. The investigated seed samples of D. lablab var. vulgaris contained higher amounts of crude protein and crude lipid when compared with most of the commonly consumed pulses. The investigated seeds were rich in minerals such as Na, K, P, Ca, Mg and Fe. Albumin and globulin fractions constituted the major bulk of seed protein. The essential amino acid profiles of total seed proteins were compared favourably with FAO/WHO (1991) requirement pattern. The fatty acid profiles of both the samples revealed that the seed lipids contained higher concentration of unsaturated fatty acids (66.78-69.08%) and had very high contents of linoleic acid (40.36-41.62%). Antinutrtional factors like total free phenolics, tannins, L-DOPA, phytic acid, hydrogen cyanide, trypsin inhibitor, oligosaccharides (raffinose, stachyose, verbascose) and phytohaemagglutinating activity were analyzed. Bangladesh J. Sci. Ind. Res. 48(2), 119-130, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15743